UTILIAZATION OF THE WISMA KARYA SUBANG MUSEUM AS A RESOURCE LEARNING SOCIAL STUDIES - Jumara, Dede Hena (Universitas Lambung Mangkurat, 2025)
The Wisma Karya Subang Museum is a learning resource that can be utilized in social studies learning. This study aims to describe the use of the Wisma Karya Subang Museum by schools in Subang Regency, the use of the Wisma Karya Subang Museum as a social studies learning resource and describe the responses of students who have visited the Wisma Karya Subang Museum. This research is a qualitative study. The techniques used for data collection are observation, interviews, and documentation. The findings of the study show that: (1) Based on the results of documentation studies and interviews, the Wisma Karya Subang Museum can already be used as a social studies learning resource and utilized by Junior High School 2 Kalijati and Junior High School 4 Subang as social studies learning resources, (2) Strategies for utilizing the Wisma Karya Subang Museum as a source of learning by IPS teachers carried out by directly bringing students to the museum environment through the implementation of P5 (Project for Strengthening Pancasila Student Profiles) and field studies using the field trip method, (3) The responses of students who have visited the Wisma Karya Subang Museum show positive things, such as students' interest in the collections available in the museum and students' enthusiasm when watching learning videos through the theater in the museum. This reflects that the Wisma Karya Subang Museum is good to serve as a social studies learning resource.